RANCANG BANGUN POWER SUPPLY ELEKTROFORESIS SEDERHANA: POTENSIAL APLIKASI UNTUK PEMISAHAN DNA/PROTEIN - Tanto Budi Susilo (Universitas Lambung Mangkurat, 2026)
Agarose gel electrophoresis is a method of separating biomolecules, based on their weight and electrical charge, such as DNA, RNA, and proteins. This method requires a stable and adjustable electrical power supply. However, commercial electrophoresis power supply devices generally have a fairly high price and are not flexible for the needs of small laboratories or practicum activities. This research aims to design and build a simple electrophoresis power supply device that is economical, and portable. The results have been designed and built two units of electrophoresis power supply 60-150 DC, 2-3 A, by engineering a 220 AC power supply, 2-3 A. The engineering process by adding diodes and digital display voltmeter. Voltage and amperage can be adjusted to the needs of gel electrophoresis. This design is compact and relatively low cost to manufacture. This independent power supply can be a viable alternative to support research and learning activities in the field of biotechnology and biochemistry.